KAJIAN TERHADAP RENCANA PENGATURAN DISGORGEMENT DALAM PASAR MODAL INDONESIA - Raysa Mayasonda; Lastuti Abubakar; Ema Rahmawati (STIH Putri Maharaja, 2020)
Various kind of capital market violations show the characteristics of capital market violations that the loss is rarely realized by the investor. Currently, the regulation provides a way to resolve investor loss of capital market and the practice of resolving violations of the law in the capital market through the investor protection regulation is sometimes not satisfactory for the harmed investors. As a step to strengthen the law enforcement instruments, the Financial Services Authority (Otoritas Jasa Keuangan / OJK) issued a Draft Regulation (RPOJK) on OJK regarding Disgorgement and Disgorgement Fund to facilitate investor’s legal protection against losses internally by itself. The purpose is to analyze the disgorgement mechanism regulation plan through the study of RPOJK so that it can be applied as a new settlement in the capital market and suitable with existing ways. The research method uses a normative juridical approach that is through the existing study of the rule of law that apply primary, secondary and tertiary legal materials, also from existing electronic literature. Based on the result of the study, it is concluded the plan of the disgorgement mechanism regulation as a form of refund through administrative mechanism is different from civil compensation and it can be applied as one of the investor’s legal protections because the form of the order in disgorgement as a refund is considered effective, proportional and can be preventive.